Kunst & Wahn - Allderidge, Patricia; Bauer, Christian; Brand-Claussen, Bettina; Brugger, Ingried; Christenson, Göran; Franzke, Andreas; Gorsen, Peter; Jadi, Ferenc; Jádi, Inge; Kraft, Hartmut; Ludwig, Thomas; Murken, Axel Hinrich; et al. (Köln : DuMont Buchverlag, 1997)
Antes, Horst ; Appel, Karel ; Artaud, Antonin ; Balla, Giacomo ; Baselitz, Georg ; Bethlem, Jonathan Martin of ; Beuys, Joseph ; Blake, William ; Bühler, Franz Karl ; Chaissac, Gaston ; Charcot, Jean Martin ; Cibber, Caius Gabriel ; Corbaz, Aloïse ; Dali, Salvador ; Dokoupil, Jiri Georg ; Dubuffet, Jean ; Duf, Gaston ; Ernst, Max ; Gabritschevsky, Eugen ; Garber, Johann ; Genzel, Karl ; Gericault, Théodore ; Gerstl, Richard ; Gie, Robert ; Goesch, Paul ; Grebing, Josef Heinrich ; Hallmann, Blalla Wolfgang ; Hauser, Johann ; Heckel, Erich ; Hill, Carl Fredrik ; Hogarth, William ; Horacek, Rudolf ; Huell, Carel Ver ; Jorn, Asger ; Josephson, Ernst ; Junker, Karl ; Kalb, Edmund ; Kaulbach, Wilhelm von ; Kirchner, Ernst Ludwig ; Kleber, Franz Joseph ; Klee, Paul ; Klett, August ; Knopf, Johann ; Kubin, Alfred ; Kurelek, William ; Lamsdorff, Graf Dimitri ; Lange, Carl ; Marcus, Otto Emil ; Masson, Andre ; Maurits, Alexander Willem ; Max ; Meryon, Charles ; Messerschmidt, Franz Xaver ; Michaux, Henri ; Munch, Edvard ; Müller, Heinrich Anton ; Natterer, August ; Navratil, Emanuel ; Nijinskij, Vaclav ; Opitz, Fritz ; Penck, A.R. ; Picabia, Francis ; Picasso, Pablo ; Pongratz, Peter ; Puga, Antonio ; Raffael-Schule ; Rainer, Arnulf ; Redon, Odilon ; Richards, Stephanie ; Richer, Paul ; Ringel, Franz ; Rubens, Pieter Paul ; Schiele, Egon ; Schneller, Joseph ; Schröder-Sonnenstern, Friedrich ; Schöpke, Philipp ; Sievers, Karl Gustav ; Signorini, Telemaco ; Sims, Charles ; Soutter, Louis ; Stuss, Otto ; Stöhrer, Walter ; Till, Josef ; Toorop, Charley ; Tschirtner, Oswald ; Vierge, Daniel ; Wain, Louis ; Walla, August ; Wols ; Wölfli, Adolf ; Xavery, Pieter ; van Gogh, Vincent
biografie
Kunst & Wahn, Kunstforum Wien, 5. September bis 8. Dezember 1997
Duits
kunstcatalogus